PENGARUH RETURN ON ASSET (ROA) TERHADAP INVESTASI AKTIVA TETAP PADA PT INTI (PERSERO) BANDUNG PERIODE 2010-2014 - Sarah Librianna; Karyadi Karyadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2017)
Abstract: This research aimed to know (1). Return On Asset (ROA) at PT INTI (Persero) Bandung (2). Fixed asset investment at PT INTI (Persero) Bandung (3). The influence of Return On Asset (ROA) to Fixed asset investment at PT INTI (Persero) Bandung. The research method used by the writer is quantitative method with descriptive analysis approach. Data collection techniques using observation techniques, literature review. The analysis technique used is normality test, product moment correlation, coefficient of determination, simple regression, and t test. The results showed that the test on the Return On Asset (ROA) to Fixed asset investment, namely Return On Asset (ROA) had an impact on Fixed asset investment which the Return On Asset (ROA) impact of 36.5% on Fixed asset investment at PT INTI (Persero) Bandung and 63.5% are influenced by other factors. Suggestions for the PT INTI (Persero) Bandung, should be better in controlling of the financial and cost efficient and also invest in fixed asset to increase revenue and others benefit.Keywords: Return On Asset (ROA), Fixed Asset Investment